3D-printing of conductive inks based flexible tactile sensor for monitoring of temperature, strain and pressure. (3rd February 2023) - Ma, Chi; Zhu, Bing; Qian, Zhihui; Ren, Lei; Yuan, Hengyi; Meng, Yunhao
Abstract: Flexible multimodal tactile sensors have been widely used in health monitoring devices, flexible smart robots, and human–machine interfaces in intelligent automobiles. In the present work, conductive inks embedded with carbon fillers were optimized to fabricate flexible multimodal tactile sensors by a direct ink writing process. Results showed that rheological properties and printing speed were key factors to print conductive paths with controllable shape and good conductivity. Flexible multimodal tactile sensors were fabricated at different printing speeds, and the effects of printing speed on sensing characteristics were observed. The flexible multimodal tactile sensors printed with conductive inks exhibited excellent sensitivities for temperature (up to 0.172 °C −1 ), strain (1918.4), and pressure (610.208 kPa −1 ). Furthermore, cyclic loading–unloading tests revealed that the as-fabricated flexible multimodal tactile sensors were reliable and durable. Finally, the application potential of these sensors for multimodal perception was verified by detecting their responses to finger flexion and extension, finger pressing, and hot air flow. The as-designed flexible multimodal tactile sensors manifested excellent potentialities in health monitoring devices, flexible smart robots, and human–machine interfaces in intelligent automobiles.